KEEFEKTIFAN KEPEMIMPINAN PENDIDIKAN SISTEM INFORMASI MANAJEMEN KEARSIPAN TERHADAP PENEMUAN KEMBALI ARSIP - Nadia Nur Wulandari; Fadila Dwi Ningtyas; Farah Milatun Nabila; M. Yazid Zaidan Nur Rizky; Siswadi (STKIP Subang, 2026)
This study aims to analyze the effectiveness of the Archival Management Information System (SIM Kearsipan) as well as the role of educational leadership in supporting records retrieval within educational organizations. A descriptive quantitative approach was employed, involving administrative staff directly engaged in records management as research subjects. Data were collected through questionnaires and analyzed using descriptive analysis, validity and reliability tests, and simple regression. The findings indicate that the implementation of the system falls into the good to very good category in enhancing the speed, accuracy, and convenience of records retrieval. Furthermore, a positive relationship was identified between the utilization of the archival information system and the effectiveness of records retrieval, with educational leadership also contributing to the optimization of system use. However, several challenges remain, including insufficient training, data entry errors, and limited facilities, which hinder system optimization. Therefore, improving user competence, continuously developing the system, and strengthening adaptive and visionary leadership support are necessary to ensure optimal system utilization. Keywords: archival management information system, effectiveness, records retrieval, educational leadership, educational administration.